Exploring the Effects of the AutisMate Application on a 12 year-old boy with ASD: A Case Study - Wall, Natalie G.; Ivey, Julie; Frederick, Karen (Journal of the American Academy of Special Education Professionals, 2019)
The study examines the effectiveness of the iPad application "AutisMate" in promoting the modeling of social communication and social interaction skills in a 12 year-old boy with Autism Spectrum Disorder (ASD). The study uses a single-subject, embedded, case study design. It calls attention to the use of assistive technology in school settings for students with Autism Spectrum Disorder. The themes explored are the participant’s independence, his social communication skills, and social interaction skills. A late theme was the participant’s non-compliant behavior in math class. Researchers found that many factors could have affected the difference on the two measures Gilliam Autism Rating Scale and Social Communication Questionnaire from pre- to post-tests, and further research is needed. There were no conclusive results that "AutisMate" had a relationship with the boy’s social interaction and communication skills.